2016
DOI: 10.1111/cod.12731
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in adult dermatitis patients stratified by filaggrin genotype

Abstract: Patients with both atopic dermatitis and common FLG mutations are more frequently affected by reduced HRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 50 publications
1
43
0
1
Order By: Relevance
“…Although some studies have shown differences in skin barrier functions (such as trans‐epidermal water loss and skin pH) between heterozygous FLG mutation carriers and wild types, others have demonstrated similar skin barrier functions in these two genotypes, in possible support of our findings . Interestingly, a recent Danish questionnaire‐based study found a dose‐dependent positive association between FLG mutations and self‐reported AK in patients with dermatitis …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although some studies have shown differences in skin barrier functions (such as trans‐epidermal water loss and skin pH) between heterozygous FLG mutation carriers and wild types, others have demonstrated similar skin barrier functions in these two genotypes, in possible support of our findings . Interestingly, a recent Danish questionnaire‐based study found a dose‐dependent positive association between FLG mutations and self‐reported AK in patients with dermatitis …”
Section: Discussionsupporting
confidence: 88%
“…25,26 A recent Dutch study found no association between AD and AK, 27 but a Danish questionnaire study in dermatitis patients shows that homozygous mutation carriers (16.7%) had a higher prevalence of self-reported AKs than heterozygous (9.0%) and wild-type carriers (2.2%). 28 In this study, we investigated the relationship between AKs and FLG mutation status, as well as the occurrence of AKs in hospitaldiagnosed patients with IV and AD, respectively, hypothesizing that individuals with a primary or secondary epidermal filaggrin deficiency would have a higher risk of AK than controls.…”
Section: Introductionmentioning
confidence: 99%
“…A positive test result was defined as a heterozygote, homozygote or compound heterozygote mutation. Patients were diagnosed with atopic dermatitis and/or hand eczema by a dermatologist at our Dermatological Department, as previously described in detail (32). In the clinic, a history of atopic dermatitis was investigated as a lifetime prevalence, whereas hand eczema was investigated as a point prevalence.…”
Section: The Patient Populationmentioning
confidence: 99%
“…Thirteen of 20 patients (65%) had a history of actinic keratosis and AD. Patients with homozygote or compound heterozygote mutations had an actinic keratosis prevalence of 16.7% versus 2.2% . Yet a Dutch study showed no association between AD and actinic keratosis and actually showed that a lower proportion of patients with AD had actinic keratosis compared with those without AD .…”
Section: Discussionmentioning
confidence: 97%
“…Patients with homozygote or compound heterozygote mutations had an actinic keratosis prevalence of 16.7% versus 2.2%. 18 Yet a Dutch study showed no association between AD and actinic keratosis and actually showed that a lower proportion of patients with AD had actinic keratosis compared with those without AD. 19 In our study, we did not specifically examine actinic keratosis; however, we did observe a statistically significant positive association between AD and SCC.…”
Section: Discussionmentioning
confidence: 99%